Study of the existence of algae, diversity of species, density, and distribution patterns in Meras waters - Kalalembang, Delarosa; Kumampung, Deislie R. H.; Angkouw, Esther D.; Lintang, Rosita A. J.; Lasut, Markus T.; Darwisito, Suria (Sam Ratulangi University, 2024)
This study aims to determine macroalgae species and analyze the index of diversity, density, dominance, and distribution patterns around the waters of Meras Village, Bunaken District, Manado. This research was carried out for 4 months starting from July – October 2023. Macroalgae sampling performed during the day was observed using the tides app to view the tides. The method used is the line transect method with the Quadrant sampling technique used to obtain data. When sampling at the research site, a total of 3 transects of 50 m were made, which were drawn perpendicular to the coastline. The distance between the transects is 25 m the distance between the quadrants is 5 m with the size of the Quadrant used to retrieve data is 1 x 1 m². The results of this study as a whole obtained 23 macroalgae species distributed in 3 divisions, namely Chlorophyta, Phaeophyta, and Rhodophyta. In the Chlorophyta Division, 8 species were obtained, then the Phaeophyta Division obtained 6 species, while the Rhodophyta Division obtained 9 species. In macroalgae data obtained in this study ranged from diversity index (H’) as a whole of transect 1 H’ = 2,537, transect 2 H’ = 2,269, while for transect 3 H’ = 1,980. Species density and relative density from transect 1 to transect 3 obtained the highest density is Padina australis. Dominance (C) overall value in transect 1 C = 0.098, transect 2 C = 0.113, while in transect 3 C = 0.153. The distribution pattern of macroalgae species in transect 1 was categorized as random, while transects 2 and 3 were categorized as clustered. Keywords: Macroalgae, Diversity, Density, Dominance, Dispersal Patterns. Abstrak Penelitian ini bertujuan untuk mengetahui spesies makroalga apa saja dan menganalisis indeks keanekaragaman, kepadatan, dominansi, dan pola penyebarannya di sekitar perairan Kelurahan Meras, Kecamatan Bunaken, Manado. Penelitian ini dilaksanakan 4 bulan mulai dari bulan Juli – Oktober 2023. Pengambilan sampel makroalga dilakukan pada siang hari diamati dengan menggunakan aplikasi tides untuk melihat pasang surut. Metode yang digunakan adalah metode garis transek (line transect) dengan teknik sampling kuadran modifikasi yang digunakan untuk memperoleh data. Saat pengambilan sampel di lokasi penelitian dibuat sebanyak 3 transek sepanjang 50 m yang ditarik tegak lurus dari garis pantai. Jarak antar transek 25 m dengan jarak antara kuadran yaitu 5 m dengan ukuran kuadran yang dipakai untuk mengambil data yaitu 1 x 1 m². Hasil pada penelitian ini secara keseluruhan diperoleh 23 spesies makroalga yang terdistribusi pada 3 divisi yaitu Chlorophyta, Phaeophyta, dan Rhodophyta. Pada divisi Chlorophyta diperoleh 8 spesies, kemudian divisi Phaeophyta diperoleh 6 spesies, sedangkan divisi Rhodophyta diperoleh 9 spesies. Pada data makroalga yang didapatkan di penelitian ini mulai dari indeks keanekaragaman (H’) secara keseluruhan dari Transek 1 H’ = 2.537, Transek 2 H’ = 2.269, sedangkan untuk Transek 3 H’ = 1.980. Kepadatan spesies dan kepadatan relatif dari Transek 1 hingga sampai Transek 3 diperoleh kepadatan tertinggi adalah Padina australis. Dominansi (C) secara keseluruhan nilai di Transek 1 C = 0.098, Transek 2 C = 0.113, sedangkan di Transek 3 nilai C = 0.153. Pola penyebaran spesies makroalga di transek 1 dikategorikan acak, sedangkan pada transek 2 dan 3 dikategorikan mengelompok. Kata kunci: Makroalga, Keanekaragaman, Kepadatan, Dominansi, Pola Penyebaran.